2005
DOI: 10.3928/0022-0124-20050101-09
|View full text |Cite
|
Sign up to set email alerts
|

Online Education: Needs Assessment for Faculty Development

Abstract: The rapidly evolving paradigm of technology-based education has increased the number of faculty teaching online. The role of faculty has changed from the traditional classroom instruction format to an online community of learning. Therefore, faculty development in online education becomes a critical component during this transitional period. A survey of faculty of the College of Applied Science and Technology in a midwestern university was conducted to identify their level of perceived expertise in online teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…This requires for not only students but teachers to become confident and competent in the new format as well. Faculty development programs need to take into account perceived faculty needs and priorities (Ali et al 2005). This can be done by integrating use of technology within low stake assessments first and shift to transforming the more crucial assessments to online format once students are at ease with the change.…”
Section: Discussionmentioning
confidence: 99%
“…This requires for not only students but teachers to become confident and competent in the new format as well. Faculty development programs need to take into account perceived faculty needs and priorities (Ali et al 2005). This can be done by integrating use of technology within low stake assessments first and shift to transforming the more crucial assessments to online format once students are at ease with the change.…”
Section: Discussionmentioning
confidence: 99%
“…Faculty development specifically designed to meet the needs of both the novice and experienced online instructor is key to the success of an online program [3,5]. Organized faculty development programs are a critical factor in the successful transition to online teaching, and ongoing support, as well as continued professional development opportunities, allows experienced instructors to keep their skills current [4,6]. Well-trained and supported faculty carry their skills into the online classroom resulting in an improved student experience and increased student satisfaction [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous instructional need assessment has shown that Faculty Members in different stages of starting and continuing their academic work, require other interdisciplinary skills in addition to their ability in their field of expertise. [5][6][7][8] This means continuation of education, research and management in various fields of medical sciences. In their college studies, they did not have the opportunity to study and work in those areas.…”
Section: Introductionmentioning
confidence: 99%